Population dynamics of the greasyback shrimp (Metapenaeus ensis, De Haan, 1844) in the Songkhla Lake, Songkhla Province, Thailand - Samphan, P.; Sukree, H.; Reunchai, T. (International Journal of Agricultural Technology, 2016)
The dynamic mathematical models (e.g., Beverton and Holt 1957, 1966), useful for predicting future yields and stock biomass at different levels of fishing strategies, are extensively used for defining management strategies. The knowledge about growth and mortality of fish populations is an essential pre-requisite for the derivation of these models. In tropical and sub- tropical waters, despite the difficulty in determining age of fish and shrimps, the dynamic pool models have, unfortunately, been under-utilized for defining management strategies in fisheries. The present study was therefore designed to investigate the population dynamics of Metapenaeus ensis in Songkhla Lake. Samples were obtained monthly for (during January 2010 to Janauary, 2011) a period of thirteen month from Songkhla Lake. The samples were collected using trap nets. The population dynamics of Metapenaeus ensis from the Songkhla Lake was investigated based on catch/effort and length frequency data, using FiSAT software. Asymptotic size (L∞), growth coefficient (K), total (Z) and natural (M) mortality, exploitation rate (E), recruitment pattern. The result showed population dynamics of Metapenaeus ensis was divided into two group.The result in group C was showed the asymptotic length (L∞) and the growth rate constant (K) were estimated to be 16.74 cm and 1.80 yr−1 . The fishing mortality coefficients were 2.50. The natural mortality was estimated at 3.16 yr−1.The instantaneous total mortality (Z) 5.66 yr−1. The exploitation ratio (E) 0.44.The result in group H was showed the asymptotic length (L∞) and the growth rate constant (K) were estimated to be 14.57 cm and 2.30 yr−1. The fishing mortality coefficients were 2.05. The natural mortality was estimated at 3.86 yr−1.The instantaneous total mortality (Z) 5.91 yr−1.The exploitation ratio (E) 0.35.